Eco-Packaging Pada Produk Wisata Kuliner Berbahan Jamu Dan Rempah-Rempah - Rahayuningsih, Handayani; Nuryani, Anik (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The experience from pre-production to enjoying the food and beverages produced, including story-telling about history, philosophy, and all things related to culinary, is a tourist attraction. The herbs and spices also enrich gastronomy tourism in Indonesia. In its development, gastronomy tourism also contributes to sustainable development, which has a positive impact on the economy, socio-culture, and the environment. However, the residues of gastronomy tourism products often cause environmental problems, especially the packaging used. This topic was raised in the study as an effort to reduce gastronomy tourism waste through the use of environmentally friendly packaging, especially for gastronomy tourism products made from herbs and spices. This research was carried out in Kemiriombo, Kulonprogo, where this location is being developed into a quality tourism destination that carries the theme of herbs and spices according to its potential. The research method used is descriptive-qualitative, with observation, interviews, literature study, and documentation as data collection techniques. The steps taken are collecting data and information related to eco-friendly packaging, identifying problems, describing the results of problem identification and findings about eco-friendly packaging, and providing recommendations for strategies for implementing eco-friendly packaging. The results of the study indicate that the choice of packaging used today is more determined by the usefulness, practicality, and price of the packaging. However, for culinary tourism products in the form of food, especially those that are part of traditional rituals such as ‘sego wiwitan’, the packaging has used environmentally friendly materials, namely banana leaves. Basically, local people already have a legacy of knowledge about loving the environment by using packaging that is sourced from nature by their ancestors, but for reasons of price and usability, currently residents do not fully use some of this heritage.